2018
DOI: 10.2139/ssrn.3294555
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Market Hypothesis and Fraud on the Market Theory A New Perspective for Class Actions

Abstract: Following recent judgement of the Supreme Court of US (June 2014), several commentators had declared that "Securities class actions are here to stay" (insidecounsel.com-September 2014, 11). This paper provides a critical perspective on this judgement, which "implicates substantive issues at the intersection of economic theory, financial markets, and securities regulation" (128 Harv. L. Rev. 291 2014-2015, 291), and shows that we must be much more careful. This recent judgement is based on the Fraud on the Mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Under the efficient market theory, the long-term price trend obeys the law of supply and demand [29]. Thus, the black swan event can only affect short-term and medium-term prices, while price manipulation can only impact market prices in a brief period.…”
Section: B Problem Definitionmentioning
confidence: 99%
“…Under the efficient market theory, the long-term price trend obeys the law of supply and demand [29]. Thus, the black swan event can only affect short-term and medium-term prices, while price manipulation can only impact market prices in a brief period.…”
Section: B Problem Definitionmentioning
confidence: 99%
“…Among various factors, agency conflict, poor corporate governance, less investor protection and specific shareholding have been found as major contributors toward market manipulation (Beasley, 1996; Huang and Cheng, 2015; Huang et al , 2012; Peng and Röell, 2013). Additionally, studies also found that poor corporate governance provides an opportunity to market manipulation with most of the time corporate managers being potential manipulators and insiders (Dissanaike and Lim, 2015; Huang and Cheng, 2015; Jovanovic et al , 2016; Peng and Röell, 2013). Studies have identified different corporate governance characteristics for manipulated stocks like board size, CEO duality, and board diversity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Madrick (2003) indicates that the presence of compensation options to top management is a significant factor of stock market manipulation as managers provide misleading information in quarterly reports to create a short-term stock price movement for personal benefits. Studies have identified that managers use private information to manipulate stock prices by trading, such as insider trading (Jovanovic et al , 2016) which is unjust and deteriorates market integrity (Dissanaike and Lim, 2015). Such examples can be traced back to Enron when managers were selling their stocks on the basis of private information, while other un-informed investors could not do so [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stock market efficiency can range from the transactions of the shares of companies to the transfer of football players (Mesagan & Amadi, 2017). In the opinion of Jovanovic et al (2016), a capital market that inspires investors to buy company shares is said to be efficient because it offers good turnover possibilities. Yet, arbitrage might still exist even if the market is efficient.…”
Section: Introductionmentioning
confidence: 99%